AN ANALYSIS OF BORAX CONTENT IN LABELED AND BULK CHICKEN NUGGETS SOLD AT TRADISIONAL MARKETS OF SURABAYA - Indriani Puspitasari; Suprijandani .; Didik Sugeng Purwanto (Poltekkes Kemenkes Surabaya, 2013)
Foodstuff constitutes any things come from biological resources and water, bothprocessed and unprocessed. One of those processed foods is chicken nugget. Nugget is aprocessedanimal product that is included in the category of easily damaged by microorganisms.Therefore, in order obtain the desired quality of food, the manufacturers often use a forbiddenadditional material such as borax that is commonly used in glass, fungicide, herbicide andinsecticide industries.This study is a descriptive type of study with cross sectional approach that is aimed tolearn about borax content in labeled and bulk chicken nuggets sold at tradisional markets ofSurabaya. The study is located at 10 traditional markets managed by PD Pasar Surya and 10markets managed individually.The result of study indicates that from the organoleptic test of 12 samples of labeledchicken nugget, 4 samples (33,3%) are hard and rubbery, 3 sampel (25%) do not have thenatural aroma of chicken meat, 6 samples (50%) have duller color and 2 samples (16,6%) haveall those three characteristics. Meanwhile, among 20 sampel of bulk chicken nugget, 14samples (70%) are hard and rubbery, 14 samples (70%) do not have the natural aroma ofchicken meat, 7 samples (35%) have duller color, and 6 samples (30%) have all those threecharacteristics. However, such an organoleptic test does not fully indicate the existence ofborax. A qualitative laboratory test by means of Turmeric Yellow PaperTest then is required. Itis found in the laboratory examination that 3 samples (25%) out of 12 samples of labeledchicken nugget positively contain borax and 7 samples (35%) out of 20 samples of bulk chickennugget positively contain borax.The market manager should cooperate with the relevant service to perform a periodicfood control. The public needs to learn about the characteristics of nugget with borax. Otherresearchers are wished to do a qualitative test of borax content on other food products or anexperiment to maintain the quality of nugget with no dangerous chemical such as borax.Keywords: Borax, labeled chicken nugget, bulk chicke